PELATIHAN OLAHAN PUDDING SAWI SEBAGAI UPAYA PENCEGAHAN DAN PENANGANAN STUNTING - Rohman, Abd.; Ka’arayeno, Arie Jefry; Putri, Santy Irene (LPPM Universitas Bina Bangsa, 2024)
Stunting prevention is designated as a national priority program by the Government of the Republic of Indonesia, by developing the National Strategy (Stranas) for the Acceleration of Stunting Prevention 2018-2024. The government targets the national stunting rate to drop to 14% in 2024. Stunting is one of the indicators of health development in the National Long-Term Development Plan (RPJPN). By 2045, the prevalence of stunting in children under five in Indonesia is targeted to reach 5 percent. The use of local food can be one of the efforts to overcome stunting, namely by utilizing local plants as food. This utilization in handling stunting can be done through cadre empowerment. In terms of human resources, Pandanrejo Village has various active organizations such as health cadres that can be mobilized to actively monitor the nutritional status of toddlers in Pandanrejo Village. Meanwhile, from the potential natural resources, one of them is mustard plants. The service activities carried out aim to increase the role of cadres in efforts to reduce stunting in Pandanrejo Village by utilizing the local potential of mustard plants. The methods carried out by the team are counseling and training. The series of service activities can be carried out well based on the results of the evaluation of the implementation team, there is an increase in the role of cadres in efforts to reduce stunting rates through the sustainability of mustard crop processing.